فاعلية برنامج بيئة التعلم الافتراضي في تعلم اللغة العربية بالمدارس الثانوية بولاية سلانجور: دراسة وصفية تحليلية - Nur Najihah Binti Mohamad Mokhtar (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study presents the effectiveness of using virtual learning environment (FROG VLE) in learning the Arabic Language among secondary school students in Selangor. The main purpose of this study is to clarify the role of VLE in learning, as well as to investigate the most preferred language activities in VLE. The researcher employs descriptive and analysis methods in conducting this research. The data was collected by using questionnaires distributed to 88 secondary students from three selected school: Sekolah Agama Menengah Bestari (SAMBEST), Sekolah Menengah Kebangsaan Agama Kuala Selangor (SMKA K.Selangor) and Sekolah Menengah Agama Persekutuan Kajang (SMAP Kajang). This study is conducted in order to utilise VLE as a platform to improve Arabic Language proficiency, and at the same time motivate students to keep learning this language. The findings show that most students tend to use electronic mail (4.10) during lessons, and they agree that VLE is entertaining (4.07) to use. From open ended questions, students claim that they enjoy learning Arabic by using forum sites. This gives them the opportunity to share information and ideas amongst themselves. Based on the findings, the study concludes that the implementation of learning Arabic through VLE has been accepted for teaching and learning Arabic as a second language.